Difficulty of predicting early-onset super-imposed preeclampsia in pregnant women with hemodialysis due to diabetic nephropathy by serum levels of sFlt-1, PlGF, and sEng - Morisawa, Hiroyuki (CEN Case Rep, 2019)
There are few case reports in which circulating levels of soluble fms-like tyrosine kinase 1 (sFlt-1), placental growth factor (PlGF), and soluble endoglin (sEng) were measured before the onset of super-imposed preeclampsia in women with hemodialysis. A 40-year-old Japanese nulliparous women with hemodialysis due to diabetic nephropathy became pregnant by frozen embryo transfer. Intensive hemodialysis was started at 5 weeks of gestation. Her blood pressure (BP) in the first trimester was around 130/80 mmHg. At 20(+3) weeks, she was admitted for close monitoring; her BP was 137/75 mmHg. Her BP increased to 157/88 mmHg at 31(+2) weeks, and nifedipine at 20 mg/day was started at 31(+6) weeks. However, the serial longitudinal measurements of sFlt-1, PlGF, and sEng did not predict the onset of super-imposed preeclampsia. Cesarean section was performed at 33(+6) weeks due to uncontrollable hypertension. A healthy female infant weighing 2138 g was delivered. As for the changes of biomarkers between just before and just after hemodialysis, sFlt-1 was significantly higher just after compared with just before hemodialysis (5774 ± 1875 pg/mL vs. 2960 ± 905 pg/mL, respectively, p < 0.001). PlGF was also significantly higher just after compared with just before hemodialysis (2227 ± 1038 pg/mL vs. 1377 ± 614 pg/mL, respectively, p < 0.001). However, the sFlt-1/PlGF ratio and sEng levels were not significantly different between just before and just after hemodialysis (p = 0.115, p = 0.672, respectively). In conclusion, prediction of early-onset super-imposed preeclampsia using angiogenic and anti-angiogenic markers in pregnant women with hemodialysis might be difficult.